Providing Care for Transgender Persons With Kidney Disease: A Narrative Review. (January 2021) - Collister, David; Saad, Nathalie; Christie, Emily; Ahmed, Sofia
Purpose of review: Nephrologists are increasingly providing care to transgender individuals with chronic kidney disease (CKD). However, they may lack familiarity with this patient population that faces unique challenges. The purpose of this review is to discuss the care of transgender persons and what nephrologists should be aware of when providing care to their transgender patients. Sources of information: Original research articles were identified from MEDLINE and Google Scholar using the search terms "transgender, " "gender, " "sex, " "chronic kidney disease, " "end stage kidney disease, " "dialysis, " "transplant, " and "nephrology." Methods: A focused review and critical appraisal of existing literature regarding the provision of care to transgender men and women with CKD including dialysis and transplant to identify specific issues related to gender-affirming therapy and chronic disease management in transgender persons. Key findings: Transgender persons are at an increased risk of adverse outcomes compared with the cisgender population including mental health, cardiovascular disease, malignancy, sexually transmitted infections, and mortality. Individuals with CKD have a degree of hypogonadotropic hypogonadism and decreased levels of endogenous sex hormones; therefore, transgender persons with CKD may require reduced exogenous sex hormone dosing. Exogenous estradiol therapy increases the risk of venous thromboembolism and cardiovascular disease which may be further increased in CKD. Exogenous testosterone therapy increases the risk of polycythemia which should be closely monitored. The impact of gender-affirming hormone therapy on glomerular filtration rate (GFR) trajectory in CKD is unclear. Gender-affirming hormone therapy with testosterone, estradiol, and anti-androgen therapies changes body composition and lean body mass which influences creatinine generation and the performance for estimated glomerular filtration rate (eGFR) equations in transgender persons. Confirmation of eGFR with measured GFR is reasonable if an accurate knowledge of GFR is needed for clinical decision-making. Limitations: There are limited studies regarding the intersection of transgender persons and kidney disease and those that exist are mostly case reports. Randomized controlled trials and observational studies in nephrology do not routinely differentiate between cisgender and transgender participants. Implications: This review highlights important considerations for providing care to transgender persons with kidney disease. Additional research is needed to evaluate the performance of eGFR equations in transgender persons, the effects of gender-affirming hormone therapy, and the impact of being transgender on outcomes in persons with kidney disease.